bacon: An Effective Way to Detect Outliers in Multivariate Data Using Stata (and Mata) - Weber, Sylvain (My University, 2010)
Identifying outliers in multivariate data is computationally intensive. The bacon command, presented in this article, allows one to quickly identify outliers, even on large datasets of tens of thousands of observations. bacon constitutes an attractive alternative to hadimvo, the only other command available in Stata for the detection of outliers.
Keywords: bacon; hadimvo; Outliers detection; Multivariate outliers.